Virtualization and forensics : a digital forensic investigator's guide to virtual environment - Barrett, Diane; Kipper, Gregory (Burlington, MA : Syngress, 2010)
Virtualization and Forensics: A Digital Forensic Investigators Guide to Virtual Environments offers an in-depth view into the world of virtualized environments and the implications they have on forensic investigations. Named a 2011 Best Digital Forensics Book by InfoSec Reviews, this guide gives you the end-to-end knowledge needed to identify server, desktop, and portable virtual environments, including: VMware, Parallels, Microsoft, and Sun. It covers technological advances in virtualization tools, methods, and issues in digital forensic investigations, and explores trends and emerging technologies surrounding virtualization technology. This book consists of three parts. Part I explains the process of virtualization and the different types of virtualized environments. Part II details how virtualization interacts with the basic forensic process, describing the methods used to find virtualization artifacts in dead and live environments as well as identifying the virtual activities that affect the examination process. Part III addresses advanced virtualization issues, such as the challenges of virtualized environments, cloud computing, and the future of virtualization. This book will be a valuable resource for forensic investigators (corporate and law enforcement) and incident response professionals.
How virtualization happens -- Server virtualization -- Desktop virtualization -- Portable virtualization, emulators, and appliances -- Investigation dead virtual environments -- Investigating live virtual environments -- Finding and imaging virtual environments -- Virtual environments and compliance -- Virtualization challenges -- Cloud computing and the forensic challenges -- Visions of the future: virtualization and cloud computing.
Includes bibliographical references and index.
Keywords: COMPUTER CRIMES -- INVESTIGATION